Renal interventions in the management of hypertension. (July 2021) - Bob-Manuel, Tamunoinemi; Amoran, Olayiwola Emmanuel; Jenkins, Christopher; Obafemi, Olushola; Tutor, Austin; Tafur, Jose
Abstract : Purpose of review: In the present comprehensive review, we describe the pathophysiology, indications, and evidence for both renal artery stenting and renal artery denervation. We also discuss the procedural techniques, risks, benefits, and future directions of renal intervention in the management of hypertension (HTN). Recent findings: Hemodynamic confirmation of lesion severity in severe renal artery stenosis is a resting or hyperemic translesional systolic gradient >20, resting or hyperemic mean translesional gradient >10 and/or renal fractional flow reserve <0.8 are considered severe. Knowing that correct stent size was used is the best predictor of restenosis, intravascular ultrasound is effective and well tolerated for stent sizing. The main categories of renal denervation: radiofrequency ablation, ultrasound, chemical ablation, and brachytherapy have shown impressive outcomes in treating resistant HTN. Summary: Over the past decade, several studies have shown the safety and benefit of catheter-based renal interventions in managing HTN. Renal artery stenting and renal artery denervation are the leading alternative invasive treatment employed in managing HTN.